2014
DOI: 10.1039/c3cp55467h
|View full text |Cite
|
Sign up to set email alerts
|

Lower critical solution temperature (LCST) phase separation of glycol ethers for forward osmotic control

Abstract: Lower critical solution temperature (LCST) phase transition of glycol ether (GE)-water mixtures induces an abrupt change in osmotic pressure driven by a mild temperature change. The temperature-controlled osmotic change was applied for the forward osmosis (FO) desalination. Among three GEs evaluated, di(ethylene glycol) n-hexyl ether (DEH) was selected as a potential FO draw solute. A DEH-water mixture with a high osmotic pressure could draw fresh water from a high-salt feed solution such as seawater through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…The water flux study corroborates well with the trend predicted using osmolality values. It is worth mentioning that the osmolality was measured by a cryoscopic method at subzero degree Celsius, thus the actual osmolality values of such LCST-type draw solutions at room temperature might be lower 27 due to stronger molecular interactions at higher temperatures. It can be observed in Fig.…”
Section: Draw Solute Performance In the Fo Processmentioning
confidence: 99%
“…The water flux study corroborates well with the trend predicted using osmolality values. It is worth mentioning that the osmolality was measured by a cryoscopic method at subzero degree Celsius, thus the actual osmolality values of such LCST-type draw solutions at room temperature might be lower 27 due to stronger molecular interactions at higher temperatures. It can be observed in Fig.…”
Section: Draw Solute Performance In the Fo Processmentioning
confidence: 99%
“…68 Density and apparent molar properties Solutions at greater concentration than 3.68 mol kg À1 visually foamed when agitated by the osmometer and thus did not freeze properly for a measurement, limiting the scope of the freezing point study.…”
Section: Freezing Point Osmometry and Higher-order Solution Statesmentioning
confidence: 99%
“…PB was once evaluated by Nakayama et al [17] and the advantages of using glycol ethers as draw solutes include low viscosities, low pH values, low volatilities, etc. On the contrary, the high pH value of the aqueous DP solution might cause potential damage to the membrane, and more caution needs to be taken during the operation because of the volatility and toxicity of DP.…”
Section: Fo Process Using Solvents With Lcst Pointsmentioning
confidence: 99%
“…Other examples of utilizing low-grade heat in draw solute recovery are the solutes with a lower critical solution temperature (LCST) point that exhibit liquid-liquid phase separation with water at high temperature. For example, Nakayama et al demonstrated that some types of glycol ethers including di(ethylene glycol) n-hexyl ether (DEH), propylene glycol n-butyl ether (PB) and di(propylene glycol) n-propyl ether (DPP) can be used as draw solutes [17]. LCST ionic liquids as draw solutes were reported to be able to treat feed solutions with NaCl concentrations of up to 1.6 mol·L −1 by Cai et al [18].…”
Section: Introductionmentioning
confidence: 99%